2019
DOI: 10.1038/s41598-019-47082-y
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb-shaped electro-neural interface enables cellular-scale pixels in subretinal prosthesis

Abstract: High-resolution visual prostheses require small, densely packed pixels, but limited penetration depth of the electric field formed by a planar electrode array constrains such miniaturization. We present a novel honeycomb configuration of an electrode array with vertically separated active and return electrodes designed to leverage migration of retinal cells into voids in the subretinal space. Insulating walls surrounding each pixel decouple the field penetration depth from the pixel width by aligning the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 46 publications
1
111
0
Order By: Relevance
“…When converting the value into human visual acuity, the result is close to 20/192, which is just within the legal blindness threshold of 20/200. Following these studies, they also proposed honeycomb-shaped electrodes for sub-retinal stimulation (Flores et al, 2019), where the stimulating electrodes sit within a deep honeycomb well, the walls of the well acting as the local returns. Experimentally (Flores et al, 2019) they demonstrated that the inner retinal cells migrated into the 25 µm deep wells after 5 weeks of implantation.…”
Section: Spatial Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…When converting the value into human visual acuity, the result is close to 20/192, which is just within the legal blindness threshold of 20/200. Following these studies, they also proposed honeycomb-shaped electrodes for sub-retinal stimulation (Flores et al, 2019), where the stimulating electrodes sit within a deep honeycomb well, the walls of the well acting as the local returns. Experimentally (Flores et al, 2019) they demonstrated that the inner retinal cells migrated into the 25 µm deep wells after 5 weeks of implantation.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…Following these studies, they also proposed honeycomb-shaped electrodes for sub-retinal stimulation (Flores et al, 2019), where the stimulating electrodes sit within a deep honeycomb well, the walls of the well acting as the local returns. Experimentally (Flores et al, 2019) they demonstrated that the inner retinal cells migrated into the 25 µm deep wells after 5 weeks of implantation. No experimental stimulating results have been published using such arrays, but from simulation, the visual acuity is expected to be better than 20/100.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…We believe that these results may improve further by introducing highly localized electrical stimuli atop and/or beside penetrating posts that support the electrode structures. Indeed, we have fabricated such high-density 3D penetrating electrode arrays for our own devices, as have other groups more recently [ 18 , 19 , 20 , 21 ], and we report on their fabrication technology below.…”
Section: Introductionmentioning
confidence: 98%
“…14 Novel electrode designs and advances in targeted stimulation strategies offer some promise for future visual prostheses. [15][16][17][18] Despite current technical limitations, users of present-day retinal implants have demonstrated improved performance in activities of daily living and in tasks involving navigation, obstacle avoidance, and light localisation (Kolic M. IOVS. 2020;61:ARVO Abstract 2199; Petoe MA.…”
Section: Introductionmentioning
confidence: 99%